O trabalho do Assistente Social no Instituto Nacional do Seguro Social/ INSS-PA: da concretização dos direitos previdenciários a operacionalização do Benefício de Prestação Continuada (BPC) - SOUZA, Leidiany Marques de (Universidade Federal do Pará, 2022)
This dissertation aimed to elucidate the political, ideological and economic determinations in the programmatic contradictions regarding the reality of the social worker's work in social security, starting in 2009, the priority attention to the demand of the BPC, social assistance policy secondary to the assistance to the Insured to access their social security rights. It is argued that the Brazilian Social Security, especially the Social Security and Social Assistance policies, suffered from the impacts of the implantation of the neoliberal governments that began in the country since the 1990s. Mainly, the commitment made by the right-wing governments and the government of the With the guidelines of the World Bank in a way that metamorphosed the concept of Social Security established by the Federal Constitution of 1988. From this debate we analyze how these determinants affect the centrality of the work of the social worker in the Brazilian Social Security , From 2009, began to prioritize the demand for the Continuous Benefit, linked to the Social Assistance Policy, secondarily providing assistance to policyholders to access their social security rights. The field research was carried out 6 agencies of the Social Security located in Belém of Pará, whose subjects were: 12 social workers, 3 medical experts and 7 managers of the respective agencies. As a data collection instrument, the semi-structured interview was applied, in addition to systematic observation. As theoretical-methodological contribution, Marx's social theory and the dialectical historical materialism method were chosen in view of the successive approximation of the real, starting from the assumption that the essence of the object to be known does not appear in the appearance of the phenomenon, Which demands of the researcher a movement of approximation with the object, that denies it, that abstracts it and that concretizes it, trying to apprehend the content of this form of work beyond its appearance, but starting from them, through the mediations of its determinations, Seeking to unveil the contradictions put in this social-occupational space. Political, ideological, and economic determinations are deeply mediated by changes in the world of work following the 1970s productive restructuring, such as unemployment, job instability, and increased informal work, when workers are unable to gain access to the protective system regulated by Social assistance policy. Still, that with an increase in the industrial reserve army, without wages, workers live in extreme poverty and, therefore, the State, through the revision of neoliberalism in its constituent bases, adopts a model in Brazil called "social liberal" where the World Bank in exchange for financial loans, implement social policies focused on this public.